2011
DOI: 10.1073/pnas.1016181108
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally and spatially configurable superlenses for optoplasmonic nanocircuits

Abstract: Energy transfer between photons and molecules and between neighboring molecules is ubiquitous in living nature, most prominently in photosynthesis. While energy transfer is efficiently utilized by living systems, its adoption to connect individual components in man-made plasmonic nanocircuits has been challenged by low transfer efficiencies that motivate the development of entirely new concepts for energy transfer. We introduce herein optoplasmonic superlenses that combine the capability of optical microcaviti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 57 publications
(76 reference statements)
2
94
0
Order By: Relevance
“…In practice, dye molecule-driven dimers are obtained in easily processable, high-purity suspensions, and exhibit accelerated single photon emission. These self-assembled nanoantennas are ideal model systems to investigate experimentally how bright and dark electromagnetic environments not only enhance 10 or shape 11 spontaneous emission but also mediate long-distance energy transfer and photochemical processes for efficient light harvesting and energy conversion 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In practice, dye molecule-driven dimers are obtained in easily processable, high-purity suspensions, and exhibit accelerated single photon emission. These self-assembled nanoantennas are ideal model systems to investigate experimentally how bright and dark electromagnetic environments not only enhance 10 or shape 11 spontaneous emission but also mediate long-distance energy transfer and photochemical processes for efficient light harvesting and energy conversion 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Under external light illumination as schematically shown in Figures 3A and B, high-intensity electromagnetic hotspots are generated in the gaps of the NP cluster ( Figure 3C) owing to the excitation and strong near field coupling of localized plasmon modes on Au NPs. The hot-spot intensities are boosted by orders of magnitude [29,[44][45][46][47] if the NP cluster is resonantly excited via the field of the WGM generated in the microcavity (compare Figure 3C and D).…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that properly arranged metallic nanoparticles can satisfy all the required RF antenna conditions, and they exhibit high directivity due to the excitation of localized surface plasmons and strong near-field interaction. Various types of optical nanoantennas have been discussed in the literature, including a hybrid design of metallic nanoparticles coupled to dielectric optical microcavities where high-Q whispering gallery modes can be used for single-molecule sensors, resonant amplifiers, nanoconcentrators, energy converters, and dynamical switches [10,11]. Similar design, consisting of a dielectric microsphere of TiO 2 with permittivity ε 1 = 6.2 and two silver nanoparticles excited by a point-like source was also considered [5].…”
Section: Introductionmentioning
confidence: 99%